4(t-4)+8t=6(2t+4)-12

Simple and best practice solution for 4(t-4)+8t=6(2t+4)-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(t-4)+8t=6(2t+4)-12 equation:


Simplifying
4(t + -4) + 8t = 6(2t + 4) + -12

Reorder the terms:
4(-4 + t) + 8t = 6(2t + 4) + -12
(-4 * 4 + t * 4) + 8t = 6(2t + 4) + -12
(-16 + 4t) + 8t = 6(2t + 4) + -12

Combine like terms: 4t + 8t = 12t
-16 + 12t = 6(2t + 4) + -12

Reorder the terms:
-16 + 12t = 6(4 + 2t) + -12
-16 + 12t = (4 * 6 + 2t * 6) + -12
-16 + 12t = (24 + 12t) + -12

Reorder the terms:
-16 + 12t = 24 + -12 + 12t

Combine like terms: 24 + -12 = 12
-16 + 12t = 12 + 12t

Add '-12t' to each side of the equation.
-16 + 12t + -12t = 12 + 12t + -12t

Combine like terms: 12t + -12t = 0
-16 + 0 = 12 + 12t + -12t
-16 = 12 + 12t + -12t

Combine like terms: 12t + -12t = 0
-16 = 12 + 0
-16 = 12

Solving
-16 = 12

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 6st-15t-10s-25= | | 2(4x+2)=-3x-9 | | 9n-26=-62 | | 37x+9=6(6x+7) | | 9x-1=4x+6 | | (X^2+2x+3)/(2x) | | 8d+d=180 | | 66x17/33x1/4 | | 2x^4+13x^2+20= | | 21x^4-4x^2-1=0 | | 4/13x=20 | | d(8)+d=180 | | 5y-2=3x-7 | | 2/-2 | | (x-3)=17 | | -(3y+3)-(2y-8)=-2 | | -10ik-2j+9k-6=-3j-k+9 | | x^5z^4/x^6z^3 | | (x-3)+(x+3)+(x+3)=17 | | 4(8x+24)=64 | | -(3y+3)-(-2-8)=-2 | | -5n-11=-46 | | x(31+-32)=629 | | 5/6x-4x+8/3=5/3 | | 2x-2y+z=2 | | x+31-x-31=629 | | 2x(5)+x(10)=640 | | 3x-2y+6z=12 | | 3x(2)+18x+15=0 | | 1.17x-0.2=0.5+0.66x | | y/3+2/5=y/5-2/13 | | 6X/7-2=40 |

Equations solver categories